2019
DOI: 10.1210/en.2018-00842
|View full text |Cite
|
Sign up to set email alerts
|

Female-Specific Role of Progranulin to Suppress Bone Formation

Abstract: Progranulin (PGRN) is best known as a glial protein for which deficiency leads to the most common inherited form of frontotemporal dementia. Recently, PGRN has been found to be an adipokine associated with diet-induced obesity and insulin resistance. Therefore, PGRN may have homeostatic effects on bone because PGRN is reported to promote the differentiation of bone-resorbing osteoclasts. We investigated the actions of PGRN on bone using PGRN gene (Grn) knockout (KO) mice and transgenic mice with PGRN mutation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 40 publications
0
8
0
Order By: Relevance
“…Increased bone resorption was not followed by up-regulated bone formation in LPS-induced bone loss, suggesting an uncoupling of bone remodeling, although a coupled bone remodeling has been shown in ovariectomy -induced [24,28] or cholesterol-induced bone loss [29]. Uncoupled bone remodeling has been reported in myeloma-related bone disease [30], and progranulin-induced bone loss in female mice [31]. In addition, uncoupling has been proposed under prolonged inflammation as a mechanism of periodontal bone loss [32].…”
Section: Discussionmentioning
confidence: 92%
“…Increased bone resorption was not followed by up-regulated bone formation in LPS-induced bone loss, suggesting an uncoupling of bone remodeling, although a coupled bone remodeling has been shown in ovariectomy -induced [24,28] or cholesterol-induced bone loss [29]. Uncoupled bone remodeling has been reported in myeloma-related bone disease [30], and progranulin-induced bone loss in female mice [31]. In addition, uncoupling has been proposed under prolonged inflammation as a mechanism of periodontal bone loss [32].…”
Section: Discussionmentioning
confidence: 92%
“…Cx3cr1 Cre is relatively more specific to the monocyte/macrophage lineage than LysM Cre , although there are also effects on neutrophils, mast cells, and classical dendritic cells [ 57 ]. These Cx3cr1 Cre mice have been the focus of much recent skeletal research [ 48 , 49 , 58 ], since there is evidence that Cx3cr1 is expressed by osteoclast precursors, which facilitates their recruitment to the BM and is downregulated when they differentiate into mature osteoclasts [ 50 , 59 ].…”
Section: Discussionmentioning
confidence: 99%
“…One model is based on the LysM Cre construct, which targets the myeloid lineage, including macrophages and preosteoclasts, and is a well-established model for specific recombination starting in early osteoclast progenitors [ 43 , 44 , 45 ]. The second model uses the Cx3cr1 Cre construct, which is more specific to macrophages but is less commonly used to study osteoclast biology [ 46 , 47 , 48 , 49 ].…”
Section: Introductionmentioning
confidence: 99%
“…Based on the sexual dimorphic bone phenotype in the ovariectomy mouse model, PGRN deficiency in the skeleton was extinguished, indicating that the source of PGRN plays a crucial role in PGRN, especially derived from microglial cells/macrophages. 57 In a murine osteoporosis model, PGRN concentration was regarded as a biomarker of disease.…”
Section: Role Of Pgrn In Osteoblastogenesis Physiologymentioning
confidence: 99%
“…Some authors have demonstrated that PGRN deficiency suppressed the expression of mature osteoclast-related genes (cathepsin K [Ctsk] and acid phosphatase 5 [Acp5]), while levels of the early osteoclast gene markers colonystimulating factor 1 receptor and adhesion G protein-coupled receptor E1 were increased. 57 With aging, TRAP and Ctsk levels gradually increased in Pgrn-KO mice, indicating enhanced osteoclastogenesis F I G U R E 2 Functions and signaling pathways associated with PGRN in osteogenesis. PGRN plays dual roles in promoting osteoblast and osteoclast differentiation.…”
Section: Role Of Pgrn In Osteoclastogenesis Physiologymentioning
confidence: 99%